Impact Analysis of Digital Transformation and Bleisure on Tourist Productivity and Hospitality Sector Revenue in Indonesia - Payu, Boby Rantow; Pontoh, Winston; Mangantar, Maryam; Murni, Sri (West Science Social and Humanities Studies, 2025)
This study investigates the impact of Digital Transformation and Bleisure (business and leisure combined) on Tourist Productivity and Hospitality Sector Revenue in Indonesia, employing a quantitative research design. A sample of 180 respondents was surveyed using a Likert scale, and the data were analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS 3). The results indicate that Digital Transformation and Bleisure have significant positive effects on both Tourist Productivity and Hospitality Sector Revenue. Specifically, Digital Transformation enhances tourist productivity by providing digital tools that facilitate efficient travel planning and execution, while also contributing to higher revenue generation in the hospitality sector by optimizing operations and customer engagement. Similarly, Bleisure significantly boosts hospitality revenue by attracting business travelers who extend their stay for leisure purposes, and it enhances tourist productivity through a more enriching travel experience. The findings suggest that the integration of digital technologies and the promotion of Bleisure travel can provide competitive advantages to businesses in Indonesia’s tourism and hospitality industries.